Change in magnesium concentration in erythrocytes in fish under stress - R. A. Zaprudnova (Regulatory Mechanisms in Biosystems, 2018)
At present, the role of erythrocyte magnesium in the respiratory processes of fish (and other animals) under conditions of stress load is not known. This article presents the results of research on change in the concentration of magnesium in erythrocytes under the action of stressors of different quality and quantity for bream (Abramis brama L.), silver crucian carp (Carassius auratus gabelio Bloch) and tench, (Tinca tinca L.) in Rybinsk Reservoir. The concentration of magnesium ions was analyzed on an atomic absorption spectrometer AAS-1 manufactured by Carl Zeiss (Germany) in the absorption regime in an air-acetylene flame. For the first time, the dependence of the change in magnesium concentration in erythrocytes on the intensity of the stress load of different nature on the example of fishes was revealed. Weak and moderate strength effects (low doses of epinephrine, norepinephrine, small changes in water temperature, saline injection, prick into the abdominal cavity, short-term removal of fish from the water, short-term keeping of fish in a limited volume of water) increased the concentration of magnesium in erythrocytes up to 2.5 times. At the same time, an increase in the affinity of hemoglobin for oxygen and a decrease in oxygen consumption were observed. However, strong stressors such as catching, transporting fish to the laboratory (representing complex effects of hypoxia, limited water volume, mechanical effects, etc.), as well as a sharp and large change in water temperature, high doses of adrenaline reduced the concentration of magnesium in erythrocytes 3 times. At the same time, the hemoglobin affinity for oxygen decreased and oxygen absorption increased. However, before the death of fish (from exhaustion), with a low level of magnesium in erythrocytes the affinity of hemoglobin for oxygen increased and the intensity of gas exchange decreased. The research conducted allow us to consider the change in the concentration of magnesium ions in erythrocytes – which are positive modulators of the affinity of hemoglobin for oxygen – in fish exposed to stress as one of the mechanisms for reducing the gas exchange intensity for weak and medium short-term stress effects and increasing it for strong short-term ones. Especially important is the role of erythrocyte magnesium as a molecular mechanism for reducing oxygen uptake and, consequently, increasing anabolism and, thus, increasing the growth and development of animals under the action of mild, short-term stressors, i.e. with eustress. In addition, the concentration of magnesium in erythrocytes can serve as an indicator of the state of fish. A high level of this cation in erythrocytes (1.5–2.0 times higher and more than normal) is characteristic for strong, healthy animals in a state of eustress or physiological stress, and extremely low values of this indicator (1.5–2.0 and more times below the norm) are an indicator of reversible or permanent ill-being (distress or pathological stress). Weakened, exhausted animals are not capable of a response to eustress or physiological stress. The possible causes of low magnesium concentrations in human erythrocytes are discussed.